ANALISIS PELAKSANAAN BUDAYA ORGANISASI DI PMI KOTA SURAKARTA - Agti, Diana; Murtini, Wiedy; Susantiningrum, Susantiningrum (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The purpose of this research are for knowing : 1) Organizational culture in Indonesian Red Cross Surakarta Region. (2) Inhibitor factor in building organizational culture in Indonesian Red Cross Surakarta Region. (3) Efforts for handling the problem in Organizational Culture in Indonesian Red Cross Surakarta Region. This research is a qualitative research with descriptive methods, case study approximation. The research strategy is single research strategy. The source of data came from informan, time and place, documents, and archive. Sampling technique that we use is Purposive Sampling and Snowball Sampling. Collecting Data are from interview, observation, and documents analysis. Data validity technique that we use are triangle data and triangle methods. Data analysis technique that we use are interactive analysis technique start from collecting data, reducing data, perform data, and conclusion. Research procedure consist of preparation step, excecution step and primary data analysis, final data analysis, conclusion, making a report, and copying reports. The conclusion of this research are: Indonesian Red Cross Surakarta Region have culture organization that are professional, perceptive and loved by people. (1) There are many way to build organizational culture in Red Cross Surakarta Region. That are (a) The person who can be a center (b) education and training for Human resources (c) regular meeting once two weeks. (2) Inhibitor factor to build organizational culture in Indonesian Red Cross Surakarta Region are : (a) Individual person (b) there just a few media to sosialize organization vision, mission, and main purpose (3) The efforts to build organizational culture in indonesian Red Cross Surakarta Region . Are : (a) Regular meeting once in 2 weeks (b) Adding media that contains organization vision, mission, and main purpose.Keyword : Culture, Organization, and Culture Organization